Nurses' Colleague Solidarity and Job Performance: Mediating Effect of Positive Emotion and Turnover Intention - Jizhe Wang; Shao Liu; Xiaoyan Qu; Xingrong He; Laixiang Zhang; Kun Guo; Xiuli Zhu (Safety and Health at Work, 2023)
Background: Job performance is known as an essential reflection of nursing quality. Colleague solidarity, positive emotion, and turnover intention play effective roles in a clinical working environment, but their impacts on job performance are unclear. Investigating the association between nurses’ colleague solidarity and job performance may be valuable, both directly and through the mediating roles of positive emotion and turnover intention. Methods: In this cross-sectional study, a total of 324 Chinese nurses were recruited by convenience sampling method from July 2016 to January 2017. Descriptive analysis, Spearman’s correlation analysis, and the structural equation model were applied for analysis by SPSS 26.0 and AMOS 24.0. Results: A total of 49.69% of participants were under 30 years old, and 90.12% of participants were female. Colleague solidarity and positive emotion were positively connected with job performance. The results indicated the mediating effects of positive emotion and turnover intention in this relationship, respectively, as well as the chain mediating effect of positive emotion and turnover intention. Conclusions: In conclusion, dynamic and multiple supportive strategies are needed for nurse managers to ameliorate nursing job performance by improving colleague solidarity and positive emotion and decreasing turnover intention based on the job demand-resource model.